2007
DOI: 10.1016/j.expneurol.2006.11.003
|View full text |Cite
|
Sign up to set email alerts
|

At-level neuropathic pain is induced by lumbosacral ventral root avulsion injury and ameliorated by root reimplantation into the spinal cord

Abstract: Neuropathic pain is common after traumatic injuries to the cauda equina/conus medullaris and brachial plexus. Clinically, this pain is difficult to treat and its mechanisms are not well understood. Lesions to the ventral roots are common in these injuries, but are rarely considered as potential contributors to pain. We examined whether a unilateral L6-S1 ventral root avulsion (VRA) injury in adult female rats might elicit pain within the dermatome projecting to the adjacent, uninjured L5 spinal segment. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 83 publications
3
54
0
Order By: Relevance
“…However, we have recently developed a rat lumbosacral ventral root avulsion (VRA) injury model, which mimics key features of the clinical CM syndrome, including denervation of pelvic targets and the development of neuropathic pain (Hoang et al, 2003(Hoang et al, , 2006aBigbee et al, 2007). A bilateral L5-S2 VRA injury in the rat is followed by urinary retention and absence of both reflex bladder contractions and EUS activity detected by electromyography (EMG), as well as increased bladder weight and size (Hoang et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…However, we have recently developed a rat lumbosacral ventral root avulsion (VRA) injury model, which mimics key features of the clinical CM syndrome, including denervation of pelvic targets and the development of neuropathic pain (Hoang et al, 2003(Hoang et al, , 2006aBigbee et al, 2007). A bilateral L5-S2 VRA injury in the rat is followed by urinary retention and absence of both reflex bladder contractions and EUS activity detected by electromyography (EMG), as well as increased bladder weight and size (Hoang et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…Minocycline may also attenuate the development of hyperesthesia and allodynia after an L5 spinal nerve transection injury in the rat (Raghavendra et al, 2003). The latter finding is of special interest to the present studies, as both transection and avulsion injuries of ventral roots may result in persistent neuropathic pain Bigbee et al, 2007). However, in some studies, minocycline treatment has failed to demonstrate beneficial effects (Smith et al 2003;Fernandez-Gomez et al 2005).…”
Section: Introductionmentioning
confidence: 55%
“…As such, we showed that a unilateral L6-S1 VRA injury induces at-level allodynia, concomitant with glial and macrophage activation in the adjacent L5 deep dorsal gray matter and dorsal funiculus (DF) ipsilateral to the lesion at 8 weeks post-injury (Bigbee et al, 2007). Importantly, acute reimplantation of the avulsed lumbosacral roots into the lateral funiculus ameliorated VRAinduced neuropathic pain and inflammation in the dorsal horn (Bigbee et al, 2007). The regions of specificity of the inflammatory response in the dorsal horn of the VRA group warrants further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental groups included: 1) sham operated controls receiving a hemi-laminectomy (Lam; n=7); 2) rats receiving unilateral avulsion of the L6-S1 ventral roots (VRA; n=9); and 3) rats undergoing unilateral L6-S1 VRA followed by immediate implantation of the avulsed roots into the lateral funiculus (Imp; n=5). The surgical procedures for the unilateral VRA procedure have been previously described (Bigbee et al, 2007). Briefly, a midline incision was made over the lumbar spine under anesthesia (2% isoflurane), and an L1-3 hemi-laminectomy was performed.…”
Section: Animals and Surgerymentioning
confidence: 99%